1975
DOI: 10.1002/cncr.2820360944
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of cancer of the colon and rectum

Abstract: The malignant potential of adenomas of the colon and rectum varies with size, histological type and grade of epithelial atypia. The adenomatous polyp is usually small and has a low malignant potential, whereas tumors with a villous structure are usually larger and have a much higher cancer rate. Severe atypia is more common in villous adenomas than in adenomatous polyps. Evidence is presented which suggests that most cancers of the colon and rectum have evolved through the polyp-cancer sequence although the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
452
5
20

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,881 publications
(489 citation statements)
references
References 38 publications
12
452
5
20
Order By: Relevance
“…It is generally accepted that there are two distinct pathways leading to the development of colorectal carcinomas: the adenoma-carcinoma sequence [1, 2]and the de novo pathway [3, 4]. The majority of early colorectal carcinomas (invasion is limited to but not deeper than the submucosa) indicates pedunculated or sessile polypoid growth and histologically carcinoma within adenomatous tissue [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that there are two distinct pathways leading to the development of colorectal carcinomas: the adenoma-carcinoma sequence [1, 2]and the de novo pathway [3, 4]. The majority of early colorectal carcinomas (invasion is limited to but not deeper than the submucosa) indicates pedunculated or sessile polypoid growth and histologically carcinoma within adenomatous tissue [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 Most colon cancers, apart from inherited genetic disorders, such as hereditary non-polyposis colorectal cancer, arise from a pre-existing polyp which develops over a period of 10-15 years into a cancer. 4 Colon cancer screening is recommended every five years from the age of 50, 2 but colorectal examinations are a contested terrain of diagnostic imaging versus optical colonoscopy (OC). This contested terrain has shifted since the introduction of newer imaging technologies, such as computed tomography colonography (CTC), 2,5,6 which is widely recognised as a highly sensitive and specific test for identifying polyps and cancer in the colon.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year survival rate of stage 1 colorectal cancer is 74%, whereas for stage 4, it drops to 6% [2] . The principle of colorectal cancer screening is based on the fact that most colorectal adenocarcinomas develop from pre-existing adenomas via numerous molecular and genetic steps, the adenoma-to-carcinoma sequence theory [3][4][5][6][7] . Fortunately, it is estimated that there is a long time interval of 10 to 15 years for the development of colorectal carcinoma from normal colon and almost 5 years for the development of adenoma from normal colon [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, by diagnosing and removing the polyps before they become malignant, it may be possible to potentially prevent invasive colorectal cancers. It has been reported that colonoscopy and polypectomy decrease the incidence of colorectal cancer by 76%-90% Apart from histology (villous has greater malignancy potential compared to tubular adenomas), polyp size is a crucial factor in determining the risk of malignancy [5] . Only about 1% of adenomas less than 1 cm in diameter turn malignant, whereas this risk rises to 10% in adenomas measuring 1-2 cm in diameter and more than 40% in those greater than 2 cm [6] .…”
Section: Introductionmentioning
confidence: 99%